On the issue of the linguistic status of adjoining constructions and dialogical units - Bohdan, Valerii (Бердянський державний педагогічний університет, 2022)
A comprehensive study of the relationship between systemic and linguistic as well as speech regularities of text organization within the processes of discretization and syncretization of its components requires a clear differentiation among text units. The attempts to identify composite syntactic units – an adjoining construction and a dialogic unity (a question and answer unity) encourage us to write again about the procedure for their distinction, which determines the relevance of this work.
Keywords: distinction; composite syntactic units; dialogic; dialogic units; adjoining construction